Oryzisolibacter propanilivorax gen. nov., sp nov., a propanil-degrading bacterium - Vaz-Moreira, Ivone (2017)
Strain EPL6T, a Gram-negative, motile, short rod was isolated from a propanil and 3,4-dichloroaniline enrichment culture produced from rice paddy soil. Based on the analyses of the 16S rRNA gene sequence, strain EPL6T was observed to be a member of the family Comamonadaceae , sharing the highest pairwise identity with type strains of the species Alicycliphilus denitrificans K601T (96.8 %) and Melaminivora alkalimesophila CY1T (96.8 %). Strain EPL6T was able to grow in a temperature range of 15–37 °C, pH 6–9 and in the presence of up to 4 % (w/v) NaCl and tested positive for catalase and oxidase reactions. The major respiratory quinone was Q8. The genomic DNA had a G+C content of 69.4±0.9 mol%. The major polar lipids were phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol, and the major fatty acid methyl esters comprised C16 : 0, C18 : 1ω7c and summed feature 3 (C16 : 1ω7c/iso-C15 : 0 2-OH). Comparison of the genome sequence of strain EPL6T and of its closest neighbours, Melaminivora alkalimesophila CY1T and Alicycliphilus denitrificans K601T, yielded values of ANI ≤84.1 % and of AAI ≤80.3 %. Therefore, the genetic, phylogenetic, phenotypic and chemotaxonomic characteristics support the classification of this organism into a new taxon. Considering the genetic divergence of strain EPL6T from the type strains of the closest species, which belong to distinct genera, we propose a new genus within the family Comamonadaceae , named Oryzisolibacter propanilivorax gen. nov., sp. nov., represented by the isolate EPL6T as the type strain of the species (=LMG 28427T=CECT 8927T).